Safety, Pharmacokinetics, and Pharmacodynamics of ASP3662, a Novel 11β‐Hydroxysteroid Dehydrogenase Type 1 Inhibitor, in Healthy Young and Elderly Subjects. Issue 3 (27th February 2019) - Bellaire, Susan; Walzer, Mark; Wang, Tianli; Krauwinkel, Walter; Yuan, Nancy; Marek, Gerard J.
Abstract : Inhibition of the enzyme 11β ‐hydroxysteroid dehydrogenase type 1 (11β‐HSD1) represents a potential mechanism for improving pain conditions. ASP3662 is a potent and selective inhibitor of 11β‐HSD1. Two phase I clinical studies were conducted to assess the safety, tolerability, pharmacokinetics (PKs), and pharmacodynamics (PDs) of single and multiple ascending doses of ASP3662 in healthy young and elderly non‐Japanese and young Japanese subjects. Nonlinear, more than dose‐proportional PKs were observed for ASP3662 after single‐dose administration, particularly at lower doses (≤ 6 mg); the PKs at steady state were dose proportional, although the time to ASP3662 steady state was dose dependent at lower doses (≤ 2 mg). Similar PKs were observed among young Japanese, young non‐Japanese, and elderly non‐Japanese subjects. Specific inhibition of 11β‐HSD1 occurred after both single and multiple doses of ASP3662. A marked dissociation between PKs and PDs was observed after single but not multiple doses of ASP3662. ASP3662 was generally safe and well tolerated.